The Use of Selected Scent Lures to Attract Terrestrial Mammals using Cmaera Traps in Kubah National Park - Kushaal, A/L Selvarajah (Universiti Malaysia Sarawak, (UNIMAS), 2017)
The study was conducted in Kubah National Park from September 2016 until April 2017. A total of 12 camera traps were mounted in the national park and was relocated once. Total of325 camera trap days and 26 species were recorded. A total of 18 terrestrial mammals was recorded over the sampling period. Moonrat (Echinosorex gymnura) recorded the highest relative abundance of 1.6686 among eight other species using Royle Nichols model. The scent lure that was able to attract the most number ofmammalian species was Calvin Klein's Obsession with a total of 16 recorded species. Correspondence Analysis (CA) showed the herbivores such as Muntiacus munijak and Tragulus napu are most attracted to the scent. A simple experiment was done to record the distance travelled by each scent lures and was recorded that Wildcat lure was able to travel the furthest of average travelled was 8.03 meters. A Generalized Linear Model (GLM) using binomial was done to compare the influence ofscent and non-scent parameter against without scent parameters and was found that the parameters of scent and non-scent does influence the outcome ofthe study.